PELATIHAN DIGITAL MARKETING DAN PERSONAL BRANDING BERBASIS E – COMMERCE UNTUK MENINGKATKAN DAYA SAING PRODUK BAGI UKM KAMPUS UNIVERSITAS TEKNOLOGI MATARAM - Muhammad Yunus (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The rapid development of digital technology has encouraged Small and Medium Enterprises (SMEs) to optimize the use of digital marketing, personal branding, and e-commerce to improve product competitiveness. However, most SMEs at Universitas Teknologi Mataram still face limitations in managing digital marketing, developing strong personal branding, and utilizing e-commerce platforms effectively. This community service program aimed to improve the knowledge and skills of SME owners through digital marketing and personal branding training based on e-commerce. The program employed a participatory approach consisting of needs assessment, training sessions, hands-on practice in developing digital promotional content, optimization of social media and marketplace platforms, and mentoring in implementing digital marketing strategies. Program evaluation was conducted through observation, discussions, and a comparison of pre-test and post-test results. The findings indicated that the training significantly improved participants' competencies across all assessed aspects. The average score increased from 50.2% in the pre-test to 83.8% in the post-test, representing an average improvement of 33.6%. The improvements covered participants' understanding of digital marketing, personal branding, e-commerce utilization, promotional content creation, and online product marketing skills. These results demonstrate that e-commerce-based digital marketing and personal branding training, supported by continuous mentoring, is effective in enhancing the digital competencies of SME owners and strengthening their product competitiveness in the era of digital transformation.